Analisis Strategi Pemasaran Coffee Shop Moja Kitchen Menggunakan Pendekatan SWOT dan Integrasi Metode Analytic Hierarchy Process dalam QSPM - Fauzan Nizami (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
This study analyzes the marketing strategy used by Coffee Shop Moja Kitchen through the SWOT (Strengths, Weaknesses, Opportunities, Threats) approach and the integration of the Analytic Hierarchy Process (AHP) method in QSPM (Quantitative Strategic Planning Matrix). The analysis was carried out to understand the competitive position of coffee shops in the market and formulate effective marketing strategies. The analysis results show that Moja Kitchen has strengths in unique customer experiences and high-quality products, but also faces challenges in competition with similar competitors and the need to increase brand visibility. The integration of the AHP method in QSPM provides a comprehensive framework for evaluating alternative marketing strategies and identifying priority actions needed to improve the marketing performance of Moja Kitchen Coffee Shop.